Mejora en el proceso logístico de la empresa de servicio electromecánico ESEM - Bonifacio Güere, Karen Juniet (2020)
The mining sector stands out for its great importance for the economic development of Peru since it is a generator of employment and foreign exchange; It’s also important to recognize and understand that we are in a globalized market with a high degree of competitiveness.This thesis was carried out with the purpose of proposing improvement proposals in the logistics process. The reduction of the delivery time of the customer service was identified as an opportunity for improvement, a qualitative analysis was carried out in order to identify the processes with the greatest impact on the reduction of the compliance rate, determining that the process with the greatest criticality and problems it was the logistics process with 35%. Within this process, a time-by-activity analysis was carried out, establishing that the activities that comprised the critical path belonged to the warehouse sub-process, where it was found that poor warehouse management increased the times of attention to requirements up to approximately 14 days. Based on these analyzes, a 5S's improvement plan and an analysis of management by processes were prepared. The program began with the implementation of 5S's as an initiative of good practices to achieve an organized, orderly, clean and safe work, in order to improve inventory search times. The second alternative of the process management solution allowed the constitution of an orderly and interrelated sequence of activities to create value in the organization, resulting in a reduction of 04 days in the last year in the attention of requirements, for this the sum of S /. 7 534,52 soles. To demonstrate the economic viability, a Benefit / Cost analysis was performed, obtaining a value of 5,64, showing that the benefits were more than five times higher than the invested cost (S /. 7 534,52), the return was also analyzed, obtaining a value of 2,13 on the invested value, which means that the payback time will return from the second month since the implementation began.